Effect of Activated Charcoal Fibers on the Survival of the House Dust Mite, Dermatophagoides pteronyssinus: A Pilot Study. (24th October 2012) - Nam, Hae-Seon; Lee, Sun-Hwa; Choi, Young-Jin; Park, Joon-Soo; Cho, Moon-Kyun; Lee, Sang-Han; Crane, Julian; Siebers, Robert
Abstract : House dust mites produce potent allergens that exacerbate asthma in sensitized patients, whom are recommended to practice allergen avoidance within their home environment. We tested the effect of activated charcoal impregnated fibers on house dust mite survival. One hundred live adult house dust mites ( Dermatophagoides pteronyssinus ) were added to eight culture dishes preequilibrated at room temperature (n = 4 ) and 70% humidity (n = 4 ) containing house dust mite food and active charcoal fibers. At 10 minute intervals, live and dead house dust mites were counted. All house dust mites instantly attached to the activated charcoal fibers and started to shrink almost immediately. There were no live house dust mites present as early as 40 minutes in some dishes while after 190 minutes all house dust mites were dead. In conclusion, activated charcoal fibers, if incorporated into bedding items, have the potential to control house dust mites in the indoor environment.